Birmanie : vers une démocratisation ou un renforcement de l'appareil dictatorial ? - Marion Sabrié (EchoGéo)
In the center of the Sino-Indian economical and strategical interests, western sanctions against the Burmese military junta appear ineffective. While the ONU makeefforts to establish a dialogue, the dictatorship seems to reinforce itself. Partly because of the divisions in the international scene, the road to democratization remains far away for the Burmesemilitary society.